PENERAPAN NILAI RELIGIUS DALAM PEMBENTUKAN KARAKTER SISWA SD 14 PILIANG BATU SANGKAR - Muhammad Hafizh (El-Rusyd, 2019)
Education in shaping the character of students in SDN 14 Piliang Batusangkar in applied with the form of structured programs with emphasis on discipline obedience and morals so as to create an effective and efficient educational goals in order to form a young generation of religious and intellectual and emotional intelligent in facing chelnged of society.